Molecular detection of Trypanosoma species and haematological alterations in four trypanosome-infected Nigerian horses - Onyinyechukwu A. AGINA; John I. IHEDIOHA; Tope E. ADEYEYE; Paschal U. UMEAKUANA; Idoko Sunday IDOKO (Notulae Scientia Biologicae, 2021)
Trypanosomes cause anaemia and are responsible for widespread morbidity and mortality particularly in imported breeds of animals found in sub-tropical and tropical parts of the world. Light microscopy and polymerase chain reaction (PCR) were used to detect trypanosomes in naturally infected Nigerian crossbred horses at Obollo-Afor abattoir, Udenu Local Government Area, Enugu State Nigeria. Blood was collected via the jugular outflow from a total of 200 horses of varying ages and either sex. Conventional procedures were followed during the PCR assay, parasite identification in wet mount, Leishman-stained thin blood and buffy coat smears on glass slides. Light microscopy revealed Trypanosoma species with an elongated, streamlined and tapered body, highly suggestive of T. brucei brucei or its subspecies T. evansi or T. equiperdum. PCR assay produced the expected fragment size of 700 bp specific for ITS-1 region of the 18SrRNA gene of Trypanosoma species in 4 (2%) of 200 blood samples against the routine blood and buffy coat smear examination, which revealed trypanosomes in 3 (1.5%) out of 200 blood samples. Sex and age were not significantly (p>0.05) associated with the trypanosome infection. One of the Trypanosoma infected anaemic horses had microcytic normochromic anaemia, high erythrocyte sedimentation rate and normal leukocyte count, while one of the Trypanosoma species infected non-anaemic horses had erythrocytic parameters and ESR values that are within the reference range, with leukocytosis. It was concluded that the prevalence of equine trypanosomosis was very low, and it’s characterized by mild to moderate anaemia in clinical cases.